2020
DOI: 10.1101/2020.06.11.20128900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations between mask-wearing, handwashing, and social distancing practices and risk of COVID-19 infection in public: a case-control study in Thailand

Abstract: Background. Effectiveness of personal protective measure against COVID-19 infection is largely unknown. Methods. We conducted a retrospective case-control study, using a cohort of contact tracing records in Thailand. A total of 1,050 asymptomatic contacts of COVID-19 patients between 1 and 31 March 2020 were retrospectively interviewed by phone about their protective measures against COVID-19 infection. Cases were defined as asymptomatic contacts who were diagnosed with COVID-19 by 21 April 2020. Multilevel … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…There has been a lot of public health messaging on face mask wearing and hand hygiene on Thai mass media channels and healthcare networks. A recent study among COVID-19 patients and their contacts in Thailand showed that wearing masks, washing hands and social distancing were strongly associated with lower risk of COVID-19 infections 18 . The evidence that mask wearing can help protect people from the infection has become more obvious, and this has resulted in updates of international guidelines related to mask wearing 19,20 .…”
Section: Discussionmentioning
confidence: 98%
“…There has been a lot of public health messaging on face mask wearing and hand hygiene on Thai mass media channels and healthcare networks. A recent study among COVID-19 patients and their contacts in Thailand showed that wearing masks, washing hands and social distancing were strongly associated with lower risk of COVID-19 infections 18 . The evidence that mask wearing can help protect people from the infection has become more obvious, and this has resulted in updates of international guidelines related to mask wearing 19,20 .…”
Section: Discussionmentioning
confidence: 98%
“…A total of 12 studies including meta-analysis, case control, cross sectional, cohort, retrospective, retrospective cross sectional, research, randomized controlled and controlled comparison studies conducted in China, United Kingdom, USA, Thailand, Uganda, Ethiopia, South Korea, Canada, and Iran were reviewed on the protective effect of masks on COVID-19 [39][40][41][42][43][44][45]. All patients had laboratory evidence of SARS-CoV-2.…”
Section: Sars-cov-2 and Masksmentioning
confidence: 99%
“…Laboratory experiments have found that almost all types of masks can greatly reduce droplet emission and viral shedding by infectious wearers 8 , 9 , suggesting their effectiveness for source control. Two observational studies 10 , 11 and recent systematic reviews focusing on SARS-1, MERS and influenza 12 15 indicate that masks also substantially reduce infection risk to the non-infected wearer, even when their infectious contact is unmasked. Specifically, Chu et al 12 suggest that the use of a surgical or cotton mask could result in a reduction in infection risk of around 44% (95% CI 11–60%) in a community setting, with stronger associations in a healthcare setting (70% [59–78%]) and using an N95 respirator (96% [70–99.6%]).…”
Section: Introductionmentioning
confidence: 99%